Pengaruh Net Profit Margin (NPM) dan Operating Profit Margin (OPM) Terhadap Pertumbuhan Laba: (Studi Pada PT. Matahari Department Store Tbk) - Yulistiawati, Alda; Huda, Nurul; Munandar, Aris (PT. Alahyan Publisher Sukabumi, 2024)
This study aims to determine and explain the influence of net profit margin (npm) and operating profit margin (OPM) on profit growth. The research method used is quantitative, with secondary data in the form of financial statements of PT. Matahari Department Store Tbk for the period of 2012-2022. Based on the results of research and data analysis regarding the Influence of Net Profit Margin (NPM) and Operating Profit Margin (OPM) on profit growth, it can be concluded that Net Profit Margin (NPM) has no partial effect on Profit Growth at PT. Matahari Tbk in 2012-2022, Operating Profit Margin (OPM) had a significant partial effect on Profit Growth at PT. Matahari Tbk in 2012-2020, Net Profit Margin (NPM), and Operating Profit Margin (OPM) simultaneously had a significant effect on Profit Growth at PT. Matahari Tbk. in 2012-2020.